RANCANG BANGUN ALAT PEMOTONG UBI-UBIAN OTOMATIS DENGAN PENDORONG PUTARAN ULIR DAN PEGAS BERTENAGA MOTOR LISTRIK (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2022)
Cassava is a food ingredient that has a high carbohydrate content. Cassava farming products are widely available in Klaten Regency. Cassava is used to make raw materials for processed food which are relatively easy to process. However, it is a pity that the processing of these sweet potatoes is still done manually, especially in the process of cutting the sweet potatoes. So we need an innovation that can facilitate the community in the processing of sweet potatoes. Based on the problems faced by cassava chip manufacturers in Klaten, an alternative solution was developed by modifying and automating a semi-automatic cassava chip making machine with a push spring. With the design of this machine, it is hoped that it can help the production of cassava chips because if the cutting is done with a machine, the time needed is shorter and the shape is more consistent.